Respuesta :

(a)

the equation of a quadratic in vertex form is

y = a(x - h)² + k

where (h, k ) are the coordinates of the vertex and a is a multiplier

here the vertex = (6, - 2 ) and a = 1

y = (x - 6 )² - 2 ← in vertex form

(b)

to find the zeros let y = 0

(x - 6 )² - 2 = 0 ( add 2 to both sides )

(x - 6 )² = 2 ( take the square root of both sides )

x - 6 = ±√2 ← ( note plus or minus )

add 6 to both sides

x = 6 ±√2 ← zeros

(c)

to obtain standard form expand the vertex form of the equation

y = x² - 12x + 36 - 2

y = x² - 12x + 34 ← in standard form